The law of law - M. Dos Santos-Lee (Law Text Culture, 1998)
Philosophy or law? Cause or effect? Does Philosophy name the laws through which things become known or are deemed as true, or must Philosophy itself be compelled by a law; guarded by an order that grants it the authority to write that such-ana-such is indeed so? And what would be the nature of such a law? What would name it as being 'true'? Philosophy? Another law? An infinite regress in the orders of Philosophy and law? ... Can we ever hope to arrive at an absolute origin in this schema, from which knowledge or truth may begin?